Peran Strategis PRM/PRA Muhammadiyah dalam Penguatan Dakwah dan Pembangunan Sosial di Desa Kertonatan: The Strategic Role of PRM/PRA Muhammadiyah in Strengthening Da'wah and Social Development in Kertonatan Village - Erni Sulistiyowati; Awalia Desvia Rahma Agzelianti; Susi Tri Susanti; ⁠Endang Wahyuningsih; Shine Afiatun Jannah; Vannisa Yunanda Aiiya Ramadanti; Anggita Dwi Hapsari; Ahmad Nurrohim (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
This article aims to examine the strategic role of PRM (Muhammadiyah Branch Leadership) and PRA (Aisyiyah Branch Leadership) in strengthening Islamic propagation (dakwah) and social development in Kertonatan Village, Kartasura District, Sukoharjo Regency. The main focus is to analyze how PRM/PRA function as both agents of religious preaching and drivers of community-based social transformation. This research adopts a descriptive qualitative approach through field observation, in-depth interviews, and documentation conducted by students of Universitas Muhammadiyah Surakarta during their community service internship (PKL-PP). The findings reveal that PRM/PRA are actively engaged not only in religious activities but also in social programs such as economic empowerment, Qur’anic education (TPA), and fostering community solidarity. However, key challenges include a lack of youth cadre regeneration and weak organizational administration. Therefore, institutional revitalization, youth leadership training, and technological adaptation are necessary strategies to optimize PRM/PRA's strategic roles. The study concludes that strengthening PRM/PRA capacity is vital for building a progressive, independent, and religiously grounded village.